Effects of Management, Dietary Intake, and Genotype on Rumen Morphology, Fermentation, and Microbiota, and on Meat Quality in Yaks and Cattle - Hu, Changsheng; Ding, Luming; Jiang, Cuixia; Ma, Chengfang; Liu, Botao; Li, Donglin; Degen, Abraham Allan (Frontiers in Nutrition, 2021)
Traditionally, yaks graze only natural grassland, even in harsh winters. Meat from grazing yaks is considered very healthy; however, feedlot fattening, which includes concentrate, has been introduced. We questioned whether this change in management and diet would have an impact on the rumen and meat quality of yaks. This study examined the morphology, fermentation, and microbiota of the rumen and the quality of meat of three groups of bovines: (1) grazing yaks (GYs, 4-year olds), without dietary supplements; (2) yaks (FYs, 2.5-year olds) feedlot-fattened for 5 months after grazing natural pasture; and (3) feedlot-fattened cattle (FC, Simmental, 2-year olds). This design allowed us to determine the role of diet (with and without concentrate) and genotype (yaks vs. cattle) on variables measured. Ruminal papillae surface area was greater in the FYs than in the GYs (P = 0.02), and ruminal microbial diversity was greater but richness was lesser in the GYs than in the FC and FYs. Concentrations of ruminal volatile fatty acids were greater in the yaks than in the cattle. In addition, both yak groups had higher protein and lower fat contents in meat than the FC. Meat of GY had a lower n6:n3 ratio than FY and FC, and was the only group with a ratio below r, which is recommended for healthy food. Essential amino acids (EAA), as a proportion of total AA and of non-essential AA of yak meat, met WHO criteria for healthy food; whereas FC did not.